Social services for children victims of domestic violence: A feminist perspective analysis in social work - Asyia, Arifah Di’Faeni Nurul; Soni Akhmad Nulhaqim (Jurnal Anifa: Studi Gender dan Anak, 2024)
Children's experiences of violence can have a significant impact on their psychological and social well-being. Social services to address these impacts are needed to restore children's social functioning. In providing such services, social workers can adopt intersectional feminist values to ensure culturally and socially sensitive social services. This article uses a literature review method of 4 books and 17 journals. A feminist perspective in social work is considered a holistic framework for understanding, addressing, and championing solutions to child abuse connected to the cultural diversity and social context of the children. This approach creates a solid foundation for social work that focuses on restoring and rebuilding the social functioning of children who have experienced violence.